THE INFLUENCE OF LEADERSHIP, COMPETENCY, AND MOTIVATION OF EMPLOYEE PERFORMANCE IN THE MINISTRY OF LAW AND HUMAN RIGHTS - Sinambela, Sarton; Simanjuntak, Erwin Marojahan; Nazmi, Mohammad Luthfy (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study is to analyze and test the influence of leadership, competence, and motivation on the performance of the State Civil Apparatus at the Regional Office of the Ministry of Law and Human Rights of DKI Jakarta. Design/methodology/approach- This research uses quantitative methods, with simple linear regression analysis and multiple linear regression with a sample size of 136 people from a population of 205 people. Multiple linear regression is used to test the hypothesis. Findings- Based on the results of multiple regression analysis, it is found that the variables of leadership, competence, and motivation together influence the performance variable. Implications- The implications of this research can be used by related parties to improve the state apparatus through empowering leaders, increasing employee competence, and motivation. Keywords: competence, motivation, leadership, performance